Synthesis & Characterization of Some 1, 3, 4-OxadiazoleDerivatives & new Cyclic Imides from Creatinine - I. Kalaf, Muna; S.Hashim, Osama (Iraqi Journal of Science, 2023)
A series of new 1,3,4- oxadiazole derivatives and cyclic Imides containing Creatinineheterocyclic molecule were prepared via following method:first step included Synthesis ofamic acid from reaction between different cyclic anhydrides with Creatinine whichsubsequently dehydrated to the corresponding imide via treatment with acetic anhydrideand anhydrous sodium acetate,.then,second step was tratedamic acid with Thionyl chlorideproducing acid chloride which on amination with hydrazine hydrate in thierd step and thelast turn to 1,3,4-oxadiazole derivatives by condensation reaction with PhosphorousOxychloride(POCl3) and different benzoic acids. Cyclization to 1, 3, 4-Oxadiazolederivatives. Antibacterial activity of some prepared new compounds against two types ofbacteria were evaluated and result showed the new exhibit good moderate antibacterialactivity.Prepared compounds were elucidated on the basis FT-IR,1H-NMR and MASSspectro data which agreed with the proposed structures.